Constitutional Reform in Iraq (Federal Supreme Court Model - طالب مصدق عادل (Journal of Legal Sciences, 2019)
This Research Deals With The Public and Private Aspects of Constitutional Reform in Iraq, and its focuses on The Organic and Substantive aspects of The Federal Supreme Court by harmonizing The Constitutional Texts with The Provisions of the Federal Supreme Court Law No. 30 of 2005 on the one hand, The constitutional and legal system currently existing with the practice of the Federal Supreme Court and the draft law of the Federal Supreme Court, the purpose of which is to achieve genuine constitutional reform that guarantees us the establishment of a constitutional institution capable of advancing its constitutional competencies according to the legal idea To the rule established by the drafters of the Constitution of the Republic of Iraq in 2005, and using the constitutional tools and mechanisms customary in the implementation of constitutional reforms.